Effects of biosorption of cadmium (II) on the external morphology and growth rate of saccharomyces cerevisiae strain 2115 - Sevilla, Almalyn C. 4 0 16; 5 (2005)
u
Thesis:(B.S. Biology)- Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2